The Economic Feasibility Analysis and Risk Asymmetry of Broiler Chicken Business Partnership Pattern in Rimbo Bujang District, Tebo Regency, Indonesia - Fikriman Fikriman; Johan Saputra; Widuri Susilawati (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
This study aims to analyze the economic feasibility of a broiler chicken farming business under a partnership model through indicators of production break-even point (BEP), price break-even point (BEP), and revenue to cost ratio (R/C) in two different production periods (2020 and 2021), as well as examining the dynamics of partnerships and business risks faced by farmers and the core company. The study used a descriptive, case-study design on a broiler farm in Perintis Village, Rimbo Bujang District, Tebo Regency. Primary data were collected through observation and in-depth interviews using a structured questionnaire, while secondary data were obtained from the literature and institutional sources. Quantitative analysis was used to calculate costs, revenue, income, BEP, and R/C, while a qualitative study was used to explain the partnership mechanism and sources of business risks. The results indicate that the broiler business under a partnership model is feasible and profitable with R/C values of 1.56 (2020) and 1.35 (2021). The production break-even point (BEP) was significantly below actual Production (2020: 12.645.65 kg vs. 106.530 kg; 2021: 14.654.61 kg vs. 130.276 kg), indicating the business was above the minimum feasibility threshold. Institutionally, the partnership provided farmers with access to capital, technical guidance, and marketing guarantees, while the core company benefited from the inputs and marketing. However, there was a risk asymmetry: farmers predominantly bore production risks, while the core company was exposed to market price fluctuations and input price increases. This finding underscores the importance of regular financial performance evaluation and the structuring of partnership contracts to strengthen the sustainability of small-scale broiler businesses. The findings of this study contribute to the economics of agribusiness and livestock farming.